IMPELEMENTASI PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA PADA MATA KULIAH PSIKOLOGI ANAK BERKEBUTUHAN KHUSUS: IMPLEMENTATION PROBLEM BASED LEARNING IN ENHANCING THE ABILITY OF CRITICAL THINKING OF PSYCOLOGY STUDENT WITH SPECIAL NEEDS - Rahman, Marlita Andhika; Pramudiani , Dessy (Jurnal Psikologi Jambi, 2024)
Introduction Problem-based learning as an effort to improve students' critical thinking skills in the Psychology of Children with Special Needs course at the Jambi University Psychology Study Programme. The findings of focus group discussions (FGDs) with alumni who work in public and special schools, experience obstacles when dealing with children with special needs, especially in observing and analysing the behaviour of developmental and learning problems in children with special needs at school. Therefore, this study aims to determine whether the implementation of problem-based learning can improve students' critical thinking skills. Method This research method uses class action with the Lewin model, the steps are: 1) Planning, 2) Action, 3) Observation, and 4) Reflection. The respondents of this study were active students of Psychology Jambi University in the Psychology of Children with Special Needs course in the academic year of the odd semester 2023/2024. The implementation lasted for one semester from August to November 2023. Results Students of Psychology in Jambi University, who contract the Psychology of Children with Special Needs course in the 2023/2024 academic year can show active behaviour and be able to provide alternative solutions to developmental and learning problems in children with special needs based on scientific studies with problem-based learning. Conclusion Problem-based learning in the psychology of children with special needs course is considered effective in improving the critical thinking skills of students of the Psychology Study Programme, Jambi University. Keyword: Problem based learning, critical thinking skills, psychology of children with special nee, college student.